2014
DOI: 10.4149/neo_2014_001
|View full text |Cite
|
Sign up to set email alerts
|

Screening differential expression of serum proteins in AFP-negative HBV-related hepatocellular carcinoma using iTRAQ –MALDI-MS/MS

Abstract: Hepatocellular carcinoma(HCC) is serious condition associated with a high morbidity and mortality. Therefore is an urgent need to develop novel noninvasive techniques for early diagnosis, particularly for patients with AFP-negative [AFP(-)] HCC. In this study, iTRAQ-MALDI-MS/MS was used to identify differentially expressed proteins in AFP(-) HBV-related HCC compared with non-cancerous hepatitis B virus (HBV) and healthy controls subjects.Serum was obtained from 18 patients with AFP(-) HBV-related HCC, 18 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 39 publications
3
51
0
1
Order By: Relevance
“…While miR-1 may play a role as a tumor suppressor gene in laryngeal carcinoma. Similarly, miR-200 is crucial for the maintenance of epithelial identity, behavior, and sensitivity to chemotherapy in ovarian cancer cell line (20,21), which confirmed our previous observation by miRNA microarrays with samples obtained from the same patients as this study (22). All these findings suggest that a functional relation is present between FN1 and platinum response, which supports our data in EOC.…”
Section: Discussionsupporting
confidence: 81%
“…While miR-1 may play a role as a tumor suppressor gene in laryngeal carcinoma. Similarly, miR-200 is crucial for the maintenance of epithelial identity, behavior, and sensitivity to chemotherapy in ovarian cancer cell line (20,21), which confirmed our previous observation by miRNA microarrays with samples obtained from the same patients as this study (22). All these findings suggest that a functional relation is present between FN1 and platinum response, which supports our data in EOC.…”
Section: Discussionsupporting
confidence: 81%
“…It participates in blood coagulation, inflammatory response, apoptosis regulation and the prevention process of metastasis in cancer cells (38,39). KNG1 is overexpressed in CRC and HCC (40) and is regarded as a potential prognostic marker for CRC, as patients with increased KNG1 expression exhibit decreased survival rates when compared with lower KNG1 expression patients (39,41). Additional studies reported that KNG1 may be involved in cholesterol and lipoprotein metabolism disturbance and take part in the complex interplay between the hemostatic system and immune response in hepatitis C virus (HCV)-associated HCC (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the isobaric tags for relative and absolute quantitation (iTRAQ) profiling technology enables the quantitative and direct comparison of the proteome changes up to 8 samples simultaneously with very high sensitivity and protein coverage [21,22]. Several groups have reported the application of iTRAQ-based quantitative proteomics approach in the study of hepatic cancer, especially for the screening of diagnostic and prognostic protein biomarkers [23][24][25]. For instance, Huang et al have reported the iTRAQ-based quantitative analysis of the recurrence/metastasis of Huge HCC (diameter is larger than 10 cm) at different stages, and identified two biomarkers for distinguishing and predicting the early recurrence/metastasis behaviors of Huge HCC [26]; Wang et al have reported the serum proteome of metastatic HCC using the iTRAQ-based quantitative analysis and identified a metastasis-associated biomarker [27].…”
Section: Introductionmentioning
confidence: 99%